ANALYSIS OF PARABOLIC MOTION IN JAVELIN THROWING INSTRUCTION: INTEGRATION OF PHYSICS AND PHYSICAL EDUCATION - Yustinus Tarigan; Awal Mulia Rejeki Tumanggor (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Modern education demands cross-disciplinary integration, including physics and physical education, to build 21st-century competencies. This article analyzes the link between parabolic motion concepts in physics and javelin throwing techniques in physical education through descriptive qualitative literature study. Findings reveal that the javelin trajectory follows parabolic motion principles, but the optimal release angle (320–360) deviates from classical physics theory (450) due to biomechanical factors such as release height (2.1–2.3 m) and modern javelin aerodynamics. Initial velocity dominates distance (75% contribution) over release angle (θ). Integrative physics-PE learning increased conceptual understanding of parabolic motion by 34% and throwing accuracy by 27%, supported by PhET simulations and sensor-based biomechanical analysis. Pedagogical implications include correcting optimal angle misconceptions, emphasizing the approach phase, and teacher collaboration via lesson study. This integration strengthens contextual scientific literacy and motor skills.